Talonavicular Coalition as a Cause of Foot Pain - Macera, Armando; Teodonno, Francesca; Carulli, Christian; Frances Borrego, Alberto; Innocenti, Massimo (Joints, 2017)
Tarsal coalitions have an incidence of 2% and are often underdiagnosed. These are considered to be one of the causes of chronic ankle and foot pain. Among all tarsal coalitions, the talonavicular type represents a rare and uncommon condition. The purpose of this article was to present the case of a 35-year-old male patient with a bilateral talonavicular coalition treated conservatively. A review of the literature was also performed to understand the management of this rare condition.
Keywords: talonavicular; tarsal; coalition; foot; treatment